PENGELOLAAN MODAL KERJA PERUSAHAAN E-COMMERCE SETELAH IPO DI BURSA EFEK INDONESIA (Studi Pada Perusahaan PT Bukalapak) - Kurniasari, Ratri; Anggraini, Asterina; Aditya, fachri (Jurnal Administrasi Profesional, 2024)
This research aims to find out how capital is managed in an e-commerce company, namely PT Bukalapak, after conducting an initial public offering based on capital management ratios which include working capital turnover, receivables turnover and cash turnover. It is known that the working capital turnover ratio in 2021 was 8.8%, then increased to 17.70% and in 2023 it was 22.91%. For 3 years from 2021 to 2023, PT Bukalapak's working capital turnover ratio increased every year. PT Bukalapak's cash turnover ratio, although in 2021 the figure for cash turnover is relatively small, namely 7.57%, however, it increases sharply in 2022 to 22.26% and 29.24% in 2023. This shows that PT Bukalapak is quite effective in managing cash. company so that it can generate increased sales.